EMERGENCY PERIPARTUM HYSTERECTOMY: FREQUENCY, INDICATIONS AND MATERNAL OUTCOME - Nisar, Nusrat; Sohoo, Nisar Ahmed (Journal of Ayub Medical College Abbottabad, 2009)
Background: Emergency Peripartum Hysterectomy (EPH), although rare in modern obstetrics, remains a life saving procedure in cases of severe haemorrhage. The aim of present study was to review the frequency, indication, associated risk factors, maternal morbidity and mortality associated with emergency peripartum hysterectomy in a private sector teaching hospital. Methods: This was a retrospective review carried out from August 2003 to September 2008. Main outcome measures were frequency, indications, associated risk factors and maternal morbidity and mortality associated with Emergency Peripartum Hysterectomy. Results: The frequency of emergency peripartum hysterectomy over a study period was 0.42%. Mean age and parity of patients was 30.9±5.0 years and 4.52±1.8 respectively. The mean gestational age at the time of delivery was 36±3.4 weeks. Nine (42.9%) patients had previous history of caesarean delivery. Main indication for EPH were rupture uterus 7 (33.3%), uterine atony 6 (28.6%), morbid adherence of placenta 5 (23.8%) and severe bleeding from placental bed in 3 (14.3%) patients. All woman required blood transfusion, 11 (52%) require ICU admission, 81% were anaemic, 3 (14.3%) developed DIC, 4 (19%) pulmonary oedema, febrile illness 6 (28.6%) and wound disruption was seen in 3 (14.3%). The maternal mortality occurred in 4 (19%) cases. Conclusion: Frequency of emergency peripartum hysterectomy is high in our set up. High parity, rupture uterus, increase number of caesarean deliveries and abnormal placentation was identified as risk factors for EPH. High frequency of maternal morbidity and mortality was observed in the present study. Keywords: Emergency Peripartum Hysterectomy, maternal morbidity, maternal mortality